2005
DOI: 10.1136/sti.2003.008557
|View full text |Cite
|
Sign up to set email alerts
|

Mexican physicians' knowledge and attitudes about the human papillomavirus and cervical cancer: a national survey

Abstract: Objective: To assess Mexican physicians' knowledge about the human papillomavirus (HPV) and cervical cancer and their opinions and practices related to screening, managing, and counselling women on these topics. Methodology: In August 2002 we surveyed 1206 general practitioners (GPs) and obstetriciansgynaecologists (Ob-Gyns) working in a nationally representative sample of public and private facilities in urban Mexico. Eligible physicians completed a self administered questionnaire. We conducted a weighted ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 9 publications
1
19
0
9
Order By: Relevance
“…Moreover, a study among Mexican physicians showed that only 19% knew that HPV types 16, 18, 31, 38 and 45 do not cause genital warts. This study showed the importance of services leading to increase of knowledge about HPV infection (Aldrich et al, 2005). There was a converse relation between the age and knowledge of parents in our study; the older parents, had less knowledge, but in the study of Stefanie et al (2010), age was not a predictor of knowledge about HPV infection (Klug et al, 2008).…”
Section: Discussionsupporting
confidence: 44%
“…Moreover, a study among Mexican physicians showed that only 19% knew that HPV types 16, 18, 31, 38 and 45 do not cause genital warts. This study showed the importance of services leading to increase of knowledge about HPV infection (Aldrich et al, 2005). There was a converse relation between the age and knowledge of parents in our study; the older parents, had less knowledge, but in the study of Stefanie et al (2010), age was not a predictor of knowledge about HPV infection (Klug et al, 2008).…”
Section: Discussionsupporting
confidence: 44%
“…An overwhelming majority of studies on acceptability of HPV vaccination among physicians have been carried out in developed countries [9][10][11][12][13][14][15][16][17][18][19]. Studies that investigated knowledge of HPV and cervical cancer have shown that awareness varies widely by specialty and training [9][10][11][12]19].…”
mentioning
confidence: 99%
“…Screening even once in a lifetime will be beneficial to avoid advanced cancer but the intervals may vary [9,10]. According to the WHO, United States Preventive Services Task Force and the American Cancer Society women should start cervical cancer screening at the age of 21 at least once every three-five year interval.…”
Section: Introductionmentioning
confidence: 99%